Capacidade anti radical livre e qualidade pós colheita de abacate Hass - Daiuto, Erica Regina [UNESP]; Cabia, Nathalie Cardoso [UNESP]; Fumes, Joana Giffoni Figueiredo [UNESP]; Vieites, Rogério Lopes [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Garcia, Márcia Regina [UNESP] (My University, 2012)
The antioxidant capacity and quality of the avocado 'Hass' was evaluated. Fruits were maintained under room temperature (24 ± 1 ºC and 70±5% relative humidity), and under refrigeration (10 ± 1 ºC and 90±5% relative humidity) for a period of 21 days. Weight losses and respiratory rates were also evaluated. Both physical and chemical characteristics were determined: titratable acidity (ATT), total soluble solids (SS), ratio, pH, firmness, polyphenoloxidase (PPO) activity, coloration (L a* b*), total phenolic and antioxidant activity for DPPH·. In both storage conditions, the breathing pick happened on the 12th storage day. Fruits maintained under refrigerated temperature presented smaller mass loss and firmness than those stored under room temperature. The ATT content decreased during storage, whereas the pH values remained stable: between 6,8 and 7,1. Brightness remained high (77.8 to 88.8%), whereas a decrease in the pulp green and yellow color components, during storage, was observed. The PPO activity decreased during storage period in fruits maintained under refrigeration, with an opposed tendency for those maintained under room temperature. Antioxidant activity and the total phenolic content decreased from beginning to end of storage. The antioxidant activity for DPPH varied from 32.5 to 20.0%.

Objetivou-se nesta pesquisa avaliar a capacidade antioxidante e qualidade do abacate ‘Hass’. Os frutos foram mantidos sob temperatura ambiente (24 ± 1 ºC e 70±5% UR) e sob refrigeração em 10 ± 1 ºC e 90±5% UR e avaliados durante 21 dias. Determinou-se a perda de massa e taxa respiratória. As características físico químicas avaliadas foram acidez total titulável (ATT), sólidos solúveis totais (SS), ratio, pH, firmeza, atividade da enzima polifenoloxidase (PPO), coloração (L a* b*), fenólicos totais e atividade antioxidante por DPPH·. Nas duas condições de armazenamento o pico respiratório ocorreu no 12º dia Os frutos mantidos sob temperatura refrigerada apresentaram menor perda de massa e firmeza em relação àqueles em temperatura ambiente. Os valores de ATT diminuiram durante o armazenamento e os valores de pH permaneceram estáveis entre 6,8 e 7,1. A luminosidade manteve-se elevada (77,8 a 88,8%), observando-se diminuição dos componentes de cor verde e amarelo na polpa com o armazenamento. A atividade da PPO diminuiu durante o período de armazenamento para os frutos mantidos sob refrigeração, com tendência oposta àqueles mantidos em temperatura ambiente. Os valores de atividade antioxidante e conteúdo de fenólicos totais diminuíram do início ao fim do armazenamento. A atividade antioxidante por DPPH variou de 32,5 a 20,0%.
Anti free radical scavenger activity and postharvest quality of Hass avocado
Keywords: Persea americana Mill.; Free radical scavenger activity; Refrigeration; Total phenolics; Persea americana Mill.; Capacidade antioxidante; Refrigeração; Compostos fenólicos